2020
DOI: 10.1016/j.gca.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Uranium isotopes in marine carbonates as a global ocean paleoredox proxy: A critical review

Abstract: The protracted oxygenation of the ocean-atmosphere system is one of the most fundamental changes to the Earth system through its history. The uranium isotopic composition (238U/235U, denoted as δ238U) of marine carbonates has been developed as a proxy to quantitatively track the timing, duration, and extent of global marine redox chemistry changes. This proxy has been applied to many critical evolutionary intervals in the last decade, significantly advancing our understanding of how life on Earth and its envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 116 publications
(311 reference statements)
2
48
0
Order By: Relevance
“…The deep-sea core samples used for this study have experienced relatively simple diagenetic histories compared to carbonates used in the majority of paleo-studies using U isotopes, which to date have focused mainly on platform carbonates and/or outcrop material 32,33,[45][46][47] . In the case of platform carbonates, that originally consisted of metastable aragonite or high-Mg calcite, diagenetic corrections are often applied to δ 238 U CAU values 33,[45][46][47] to account for authigenic U(IV) uptake under reducing porewater conditions during early diagenesis (including recrystallization and cementation) that results in a high degree of scatter with a generally positively offset compared to seawater (~+0.27 ± 0.14‰; 1 SD) 48,49 . Previous work has suggested that some pelagic carbonates record lower δ 238 U CAU signatures, closer to seawater values compared to platform counterparts, and thus do not require correction 32,41 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The deep-sea core samples used for this study have experienced relatively simple diagenetic histories compared to carbonates used in the majority of paleo-studies using U isotopes, which to date have focused mainly on platform carbonates and/or outcrop material 32,33,[45][46][47] . In the case of platform carbonates, that originally consisted of metastable aragonite or high-Mg calcite, diagenetic corrections are often applied to δ 238 U CAU values 33,[45][46][47] to account for authigenic U(IV) uptake under reducing porewater conditions during early diagenesis (including recrystallization and cementation) that results in a high degree of scatter with a generally positively offset compared to seawater (~+0.27 ± 0.14‰; 1 SD) 48,49 . Previous work has suggested that some pelagic carbonates record lower δ 238 U CAU signatures, closer to seawater values compared to platform counterparts, and thus do not require correction 32,41 .…”
Section: Resultsmentioning
confidence: 99%
“…The invariance of the Site 865 record is taken to indicate the lack of a resolvable perturbation to the global U isotope mass balance during the PETM. Here we use an established biogeochemical box model 32,47 to assess the quantitative implications of this result. We use the Site 865 δ 238 U CAU dataset and higher resolution δ 13 C data from Site 401 (ref.…”
Section: Resultsmentioning
confidence: 99%
“…The carbonates samples were then crushed into fine powder using an agate mortar and pestle, and the carbonate content was estimated from major element abundances determined on compacted powder pellets using a JEOL JSM-5800LV scanning electron microscope (SEM). The carbonate content was used to calculate the amount of acid to add to each sample to fully digest the carbonate fraction without leaching detrital phases (Tissot et al 2018;Clarkson et al 2020;Zhang et al 2020b).…”
Section: Methodsmentioning
confidence: 99%
“…Excluding dolomitic units would also leave large gaps in the carbonate archive. Instead, for some intervals, we have analyzed both limestones and dolostones to assess the effect of dolomitization on uranium isotopic ratios (see also the discussions in Herrmann et al 2018;Zhang et al 2020aZhang et al , 2020b.…”
Section: Samplesmentioning
confidence: 99%
See 1 more Smart Citation